Caspase‐1 inflammasome activity in patients with Staphylococcus aureus bacteremia. (16th October 2019) - Rasmussen, Gunlög; Idosa, Berhane Asfaw; Bäckman, Anders; Monecke, Stefan; Strålin, Kristoffer; Särndahl, Eva; Söderquist, Bo
Abstract: The inflammasome is a multiprotein complex that mediates caspase‐1 activation with subsequent maturation of the proinflammatory cytokines IL‐1β and IL‐18. The NLRP3 inflammasome is known to be activated by Staphylococcus aureus, one of the leading causes of bacteremia worldwide. Inflammasome activation and regulation in response to bacterial infection have been found to be of importance for a balanced host immune response. However, inflammasome signaling in vivo in humans initiated by S. aureus is currently sparsely studied. This study therefore aimed to investigate NLRP3 inflammasome activity in 20 patients with S. aureus bacteremia (SAB), by repeated measurement during the first week of bacteremia, compared with controls. Caspase‐1 activity was measured in monocytes and neutrophils by flow cytometry detecting FLICA (fluorescent‐labeled inhibitor of caspase‐1), while IL‐1β and IL‐18 was measured by Luminex and ELISA, respectively. As a measure of inflammasome priming, messenger RNA (mRNA) expression of NLRP3, CASP1 ( procaspase‐1 ), and IL1B ( pro‐IL‐1β ) was analyzed by quantitative PCR. We found induced caspase‐1 activity in innate immune cells with subsequent release of IL‐18 in patients during the acute phase of bacteremia, indicating activation of the inflammasome. There was substantial interindividual variation in caspase‐1 activity between patients with SAB. We also found an altered inflammasome priming with low mRNA levels of NLRP3 accompanied by elevated mRNA levels of IL1B . This increased knowledge of the individual host immune response in SAB could provide support in the effort to optimize management and treatment of each individual patient.